STAY OR LEAVE ? HOW DIGITAL UPSKILLING SHAPES LOYALTY AND REDUCES TURNOVER IN GENERATION Z EMPLOYEES - Dewi Tri Komalasari; Abdul Rahman Rahim (PT Wahana Global Education, 2026)
This study aims to analyze the role of digital upskilling in shaping loyalty and reducing turnover of generation z. Generation Z is known to be adaptive to technology and has high expectations for self-development, so companies need to respond through digital upskilling programs. This study used a descriptive qualitative approach with purposive sampling technique, involving 9 generation Z participants aged 22-28 years old who had participated in digital training. Data were collected through semi-structured interviews and analyzed thematically. The results showed that (1) digital upskilling is perceived as a form of corporate concern for employee development; (2) self-development opportunities increase loyalty through emotional attachment; and (3) the absence of training creates a feeling of stagnation that triggers turnover intentions. These findings reinforce Social Exchange Theory, where reciprocal relationships between companies and employees play a role in creating loyalty. The research recommends that companies make digital upskilling an ongoing program with flexible methods such as e-learning, and link it to career paths to retain generation Z talent.